The design and construction of post tensioned flat slab - Zakaria, Nurhidayah (2011)
Post tensioning flat slab are not complex where the construction technique, structure behavior and design are all simple. The tendon install provide a suspension system within the slab and the simple balancing load were used. The principle of designing post-tensioning flat slab is based on the parabolic tendon profile which exerts to upward pressure and balance to the downward loading. The installation of post tensioning system should be done by experience personnel who can handle the problems occurs while installing, stressing and grouting process. This paper presents the results of case studies on two post tensioned pre-stressed flat slabs in which save in using reinforcement, helps in deflection and also provide head clearance for Mechanical and Electrical components to run.